Trimetazidine attenuates pressure overload-induced early cardiac energy dysfunction via regulation of neuropeptide Y system in a rat model of abdominal aortic constriction. Issue 1 (December 2016) - Chen, Ailan; Li, Wanglin; Chen, Xinyu; Shen, Yuechun; Dai, Wenjun; Dong, Qi; Li, Xinchun; Ou, Caiwen; Chen, Minsheng
Abstract Background Metabolism remodeling has been recognized as an early event following cardiac pressure overload. However, its temporal association with ventricular hypertrophy has not been confirmed. Moreover, whether trimetazidine could favorably affect this process also needs to be determined. The aim of the study was to explore the temporal changes of myocardial metabolism remodeling following pressure-overload induced ventricular hypertrophy and the potential favorable effect of trimetazidine on myocardial metabolism remodeling. Methods A rat model of abdominal aortic constriction (AAC)-induced cardiac pressure overload was induced. These rats were grouped as the AAC (no treatment) or TMZ group according to whether oral trimetazidine (TMZ, 40 mg/kg/d, for 5 days) was administered. Changes in cardiac structures were sequentially evaluated via echocardiography. The myocardial ADP/ATP ratio was determined to reflect the metabolic status, and changes in serum neuropeptide Y systems were evaluated. Results Myocardial metabolic disorder was acutely induced as evidenced by an increased ADP/ATP ratio within 7 days of AAC before the morphological changes in the myocardium, accompanied by up-regulation of serum oxidative stress markers and expression of fetal genes related to hypertrophy. Moreover, the serum NPY and myocardial NPY-1R, 2R, and 5R levels were increased within the acute phase of AAC-induced cardiac pressure overload. Pretreatment with TMZ could partly attenuate myocardial energy metabolic homeostasis, decrease serum levels of oxidative stress markers, attenuate the induction of hypertrophy-related myocardial fetal genes, inhibit the up-regulation of serum NPY levels, and further increase the myocardial expression of NPY receptors. Conclusions Cardiac metabolic remodeling is an early change in the myocardium before the presence of typical morphological ventricular remodeling following cardiac pressure overload, and pretreatment with TMZ may at least partly reverse the acute metabolic disturbance, perhaps via regulation of the NPY system.